2017
DOI: 10.1155/2017/4310475
|View full text |Cite
|
Sign up to set email alerts
|

TBHQ Alleviated Endoplasmic Reticulum Stress‐Apoptosis and Oxidative Stress by PERK‐Nrf2 Crosstalk in Methamphetamine‐Induced Chronic Pulmonary Toxicity

Abstract: Methamphetamine (MA) leads to cardiac and pulmonary toxicity expressed as increases in inflammatory responses and oxidative stress. However, some interactions may exist between oxidative stress and endoplasmic reticulum stress (ERS). The current study is designed to investigate if both oxidative stress and ERS are involved in MA-induced chronic pulmonary toxicity and if antioxidant tertiary butylhydroquinone (TBHQ) alleviated ERS-apoptosis and oxidative stress by PERK-Nrf2 crosstalk. In this study, the rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…Tertiary butylhydroquinone (TBHQ), a commonly used food antioxidant permitted by China (Health Standard GB2760.2011), is widely found in oils, biscuits, and other foods. The bodily oxidation of TBHQ can provide H+ radicals, which can stop the reaction and thus play an antioxidant role [33]. Furthermore, TBHQ induces phase II enzymes and the Nrf2 signaling pathway and shows remarkable antioxidant activity in various cell types and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Tertiary butylhydroquinone (TBHQ), a commonly used food antioxidant permitted by China (Health Standard GB2760.2011), is widely found in oils, biscuits, and other foods. The bodily oxidation of TBHQ can provide H+ radicals, which can stop the reaction and thus play an antioxidant role [33]. Furthermore, TBHQ induces phase II enzymes and the Nrf2 signaling pathway and shows remarkable antioxidant activity in various cell types and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to METH also altered the expression of the mRNAs involved in the oxidative phosphorylation pathway (Wang et al, 2017b) in which cells use enzymes to oxidize nutrients and then to produce adenosine triphosphate. Some studies have reported that oxidative phosphorylation capacity in the mitochondria would be altered and would influence cellular function (Kim, Chin & Cho, 2017;Xia et al, 2014;Xu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The rats in the control group were injected with an equal volume of 0.9% physiological saline solution. 23 All rats were raised in a room with controlled temperature (18-22°C) and humidity (50%-70%) and were fed with solid food and water in an alternating 12 hours light and 12 hours dark cycle. All experimental procedures involving animals were followed by the guidelines of…”
Section: Resource Center China Medical University (Certificate Numbermentioning
confidence: 99%